Effect of severe dietary magnesium deficiency on systemic bone density and removal torque of osseointegrated implants - Barrio, Ricardo Andrés Landázuri Del [UNESP]; Giro, Gabriela [UNESP]; Belluci, Marina Montosa [UNESP]; Pereira, Rosa Maria Rodrigues; Marcantonio, Elcio [UNESP]; Massucato, Elaine Maria Sgavioli [UNESP]; Orrico, Silvana Regina Perez [UNESP] (My University, 2010)
Purpose: This study evaluated the effect of severe magnesium (Mg) dietary deficiency on systemic bone density and biomechanical resistance of bone tissue to the removal torque of osseointegrated implants. Materials and Methods: The sample consisted of 45 rats; each received a titanium implant in their tibial metaphysis. After 60 days, the animals were divided into three groups (n = 15) according to their dietary Mg: the control group received the recommended content of Mg, group Mg1 received a 75% reduction in dietary Mg content, and group Mg2 was fed a diet with a 90% reduction in Mg content. Animals were sacrificed 150 days after implant placement. Serum concentrations of Mg were measured and the effect of Mg deficiency on systemic bone density was evaluated by densitometry of the lumbar vertebrae and femur. Biomechanical characteristics were measured by resistance of the bone tissue to removal of the implants. Results: Lower Mg serum concentrations were found for the Mg1 and Mg2 groups; however, densitometric analysis and torque evaluations showed a statistically significant difference only in the Mg2 group (P < .05). There was a statistically significant difference in removal torque between the Mg2 group and the control group. Conclusions: This study showed that a severe deficiency of Mg decreased the systemic bone density and removal torque of osseointegrated implants. © 2010 by Quintessence Publishing Co Inc.
Keywords: Bone mineral density; Dental implants; Magnesium deficiency; Rats; Removal torque